A LEGAL AND POLICY CONSIDERATIONS FOR OBTAININGEFFECTIVE CRISIS MANAGEMENT IN THE REPUBLIC OF MACEDONIA - Poposka, Vesna (International Scientific Journal Vision, 2019)
Crises are an integral part of social processes and everyday life. The art of dealing with them, the ability to predict and prevent, and the effectiveness in the alleviation of their consequences, is what predefines the development of the society as a whole-it is defined by the resilience and the fast recovery.The institutional structure isthe key for establishing the mechanisms, and it is the normative framework that predefines it, converted into a legal and sub legal acts. The text aims to look at the current institutional arrangements for crisis management in the Republic Macedonia andsee if it suits the purpose of crisis management in general, as well as some comparative expereinece as a suggestions for implementation of legal reforms, as precodnsition for obtaining effective institutional framework for implementation.